Optimization of Stearic Acid and Triethanolamine in The Antibacterial Cream Staphylococcus aureus Ethanol Extract of Papaya Seeds (Carica papaya L.): Factorial Design Method - Jacinda Yakub; Wahyuning Setyani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
The ethanol extraction of papaya seeds provides a synergistic inhibitory effect on Staphylococcus aureus thorugh alkaloids, flavonoids, tannins and saponins. In this research, the ethanol extract of papaya seeds was formulated in cream preparations and optimized. The optimization of stearic acid as the oil phase and TEA as the water phase resulted in a cream with good physical properties and stability. The parameters used to observe the physical properties and stability of the ethanol extract cream of papaya seeds were organoleptic, homogeneity, pH, centrifugation, viscosity, spreadability, and adhesion. Optimization data analysis using Design Expert 12 free trial. The result of optimization is stearic acid contributed most dominantly to the response to increase viscosity by 73.739% and adhesion by 91.695%, while TEA contributed to the increased in dispersibility by 13.107%. The optimum amount of composition used for stearic acid was 5 grams and TEA was 2 grams. The research showed that inhibitory activity of papaya seed ethanol extract at a concentration of 20% was classified as moderate. However, at concentrations of 40%, 60%, 80%, and 100%, the inhibitory activity is quite strong.